Menilai Kepuasan Produk Menggunakan CSI Berdasarkan Respons Konsumen - Nasyuha, Asyahri Hadi; Habibie, Dedi Rahman; Kurniawati, Deborah; Suryati, Pulut (Universitas Mercu Buana, 2025)
The main issue addressed in this research is identifying the factors that influence customer satisfaction and understanding how well a product meets customer expectations. A questionnaire was distributed to collect data from consumers, and the CSI method was applied to assess the overall satisfaction level based on key aspects such as Product quality, Product durability, Price, Service, Purchasing process and Shipping process. The results showed that most consumers were satisfied with the product, with quality and after-sales service being the most significant factors contributing to overall satisfaction. However, areas such as pricing and ease of use were identified as needing improvement. The study also found that the CSI method provides a reliable means of measuring customer satisfaction and offers valuable insights into areas for product improvement. Based on the findings, the research suggests focusing on enhancing after-sales service and adjusting pricing strategies to better meet consumer expectations. Further research could expand the study to include external factors such as market competition and industry trends, while incorporating advanced analytical methods like regression analysis or machine learning for more in-depth predictions of customer satisfaction.